LEGAL REGULATION OF EUROPEAN HIGHER EDUCATION AND LEGAL BASES OF INSTITUTIONAL CAPACITY OF UKRAINIAN UNIVERSITIES - Коваленко, О. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article examines the legal bases of the European universities’ institutional capacity, based on international legal acts in the field of education. «Standards and Guidelines for Quality Assurance in the European Higher Education Area» were designed in order to improve the universities operations. The scientific sources and legal documents which are regulating the legal bases of the universities’ institutional capacity, the process of European integration of Ukrainian higher education and experience of European universities actions in Ukraine were analysed. Achievements and challenges by the higher education of Ukraine, its ways for overcoming the integration of institutional capacity into the European community are determined